Rhyacoschistura larreci, a new genus and species of loach from Laos and redescription of R. suber (Teleostei: Nemacheilidae) - Kottelat, Maurice (Zootaxa, 2019)
Rhyacoschistura, new genus, belongs to a group of genera (Physoschistura, Mustura, Pteronemacheilus, Petruichthys) characterised by the modified branched pectoral-fin rays of males, with a very thick first ray, usually without membranes between some of the branches and/or rays, and anterior rays and/or membranes covered by small tubercles at maturity. Rhyacoschistura is distinguished from them by the combination of: presence of a suborbital flap; emarginate caudal fin; lower lip with a wide median interruption and connected to isthmus by a frenum; body depth about equal from behind head to caudal-fin base. Rhyacoschistura larreci, new species, is described from the Mekong drainage in Xayaburi Province, Laos. It is distinguished by details of the morphology of the pelvic fin, and its colour pattern (flank with numerous narrow slanted bars, very irregularly organised and shaped, more or less connected, or sometimes covering the whole flank). Schistura suber, from Nam Ngum watershed, is redescribed on the basis of adults and placed in Rhyacoschistura.